Corporate governance mechanisms in theory and practice of housing cooperatives - Brzeska, Aneta; Mazurczak-Mąka, Anna (Mechanizmy nadzoru korporacyjnego w teorii i praktyce spółdzielni mieszkaniowych, 2019)
The research goal is to present the results of research on corporate governance mechanisms used by supervisory boards when assessing the management of the activities of Polish housing cooperatives. To achieve this goal, the essence of corporate governance and its mechanisms in relation to housing cooperatives were analyzed, followed by empirical research whose respondents were members of supervisory board. The research object is a housing cooperative operating in Poland. Achievement of the objectives of the article was possible due to an in-depth study of domestic and foreign literature related to the topic of the work, as well as the application of the survey method
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 4, s. 10-17
Keywords: housing cooperative; oversight mechanisms; corporate governance; supervisory board; audit; spółdzielnie mieszkaniowe; nadzór korporacyjny; rady nadzorcze; nadzór spółdzielczy; audyt